Interface engineering for high-performance direct methanol fuel cells using multiscale patterned membranes and guided metal cracked layers. (January 2018) - Jang, Segeun; Kim, Sungjun; Kim, Sang Moon; Choi, Jiwoo; Yeon, Jehyeon; Bang, Kijoon; Ahn, Chi-Yeong; Hwang, Wonchan; Her, Min; Cho, Yong-Hun; Sung, Yung-Eun; Choi, Mansoo
Abstract: Capability to fabricate high-performance membrane electrode assemblies (MEAs) is a key to the commercialization of direct methanol fuel cells (DMFCs). This work reports an interface engineering method to introduce a multiscale patterned membrane and a guided metal cracked layer between the catalyst layer and the membrane by the creep-assisted sequential imprinting and simple stretching technique. The MEA with a multiscale patterned membrane, where the nanopatterns covered the whole surface even on the side surface of microstructures, showed improved performance owing to enhanced mass transport by the thinned electrode, effective utilization of the active sites, and increased Pt utilization. To obtain further performance enhancement, we incorporated a guided gold cracked layer into the MEA with the multiscale patterned membrane. The electrochemically inactive thin gold layer acted as a physical barrier for methanol crossover and the guided cracks provided multiple proton pathways. Our interface engineering utility resulted in an enhancement of the device performance by 42.3% compared with that of the reference. Graphical abstract: Highlights: Interface engineering was employed to develop a high-performance DMFC. A creep-assisted sequential imprinting and simple stretching method was used. Enlarged membrane–electrode interface improved anode kinetics and mass transport. Au layer blocked methanol crossover while cracks maintained proton conductivity. Multiscale patterned membrane/guided Au cracked layer improved device performance.